Time course and prognostic impact of venoarterial extracorporeal membrane flow throughout cardiogenic shock. (2nd May 2022) - Montero, S; Huang, F; Rivas-Lasarte, M; Chommeloux, J; Brechot, N; Hekimian, G; Franchineau, G; Luyt, CE; Garcia-Garcia, C; Bayes-Genis, A; Lebreton, G; Cinca, J; et al.
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: In VA-ECMO supported patients because of refractory cardiogenic shock (CS), there is a lack of evidence on what is the "optimal" ECMO flow. Purpose: To describe the evolution of VA-ECMO flow in a CS population according to the degree of support and analyze the impact of early high-ECMO flows on short-term outcomes. Methods We performed a retrospective, single-center study including patients in refractory CS supported with peripheral VA-ECMO admitted at an University Hospital. Based on the median flow over the first 48 hours of ECMO run, patients were classified as "high-flow" or "low-flow" when median ECMO flow was ⋝ or < than 3.6 L/min, respectively. All statistical tests were two-sided, with a p value ≤ 0.05 considered significant. Results: Two hundred and nine patients were included. Median age was 51 (40-59) years, 78% were males, and the median SAPS II was 51 (32 - 66). The most frequent etiology leading to CS was end-stage-dilated cardiomyopathy (57%). "High-flow" and "low-flow" groups each represented 50% of the study population, respectively (Figure 1). Median flows between both groups were continuously lower in "low-flow" patients at any time-point, with the "low-flow" group maintaining VA-ECMO flows around 3.0-3.1 L/min. The "high-flow" group had a higher frequency of ischemic etiology and was significantly sicker at admission. Almost 70% of the study population was managed with LV unloading. More than 40% of patients were managed with an awake strategy, with much higher rates of awake ECMO in the "low-flow" group (52% vs 30%, p<0.001). Patients with "high-flow" had 50% more VAP than "low-flow" patients and median days on mechanical ventilation were significantly less in the "low-flow" group (4 [1.5 - 7.5] vs 6 [3 - 12] days, p=0.009, respectively). No differences were either found in total days in ICU or days of hospitalization. Finally, global in-hospital mortality was 46%, with less but not statistically significant differences in the "low-flow" group (41% vs 51%, p=0.144, respectively). Mortality at 60-days were alike for both groups. Conclusions: In patients with refractory CS supported with VA-ECMO, sicker patients were managed with higher degree of support from early phases. Patients with high flows presented with higher rates of VAP, but presented similar in-hospital and short-term survival compared to patients with lower flows. Future research is now warranted to address the specific, direct, impact of higher flows in lung injury or length of MV.